2000
DOI: 10.1006/dbio.2000.9668
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Early Transcription in One-Cell Mouse Embryos by Microinjection of the Nonhistone Chromosomal Protein HMG-I

Abstract: In the mouse embryo, the onset of zygotic transcription occurs at the end of the first cell cycle, upon completion of DNA replication. We show that the nonhistone chromosomal protein HMG-I, whose translocation into the pronuclei of one-cell embryos is linked to this first round of DNA synthesis, plays a critical role in the activation of zygotic transcription. Indeed, microinjection of purified HMG-I results in a higher nuclear accumulation of the protein and triggers an earlier activation of zygotic transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 51 publications
(49 reference statements)
0
29
0
1
Order By: Relevance
“…For example, the onset of transcription in one-cell mouse embryos depends on the amount of HMGA1a, probably due to a competitive displacement of histone H1 or other general repressors, making chromatin regions accessible to the transcription machinery (Beaujean et al, 2000). In addition, only transgenic mice expressing high levels of truncated HMGA2 lacking the acidic C-tail showed an increased adiposity and a giant phenotype (Battista et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the onset of transcription in one-cell mouse embryos depends on the amount of HMGA1a, probably due to a competitive displacement of histone H1 or other general repressors, making chromatin regions accessible to the transcription machinery (Beaujean et al, 2000). In addition, only transgenic mice expressing high levels of truncated HMGA2 lacking the acidic C-tail showed an increased adiposity and a giant phenotype (Battista et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear translocation of p100 prp1/zer1/prp6 seems to be closely linked to the onset of the minor ZGA which occurs at the late 1-cell stage. It has been reported that the nuclear concentrations of SP1, TBP [8], HMG-1 [10], RPB1 [9], and snRNPs [17] in mouse 1-cell embryos also increase during the 1-cell stage. It has been antibody.…”
Section: Discussionmentioning
confidence: 99%
“…During the transcriptionally inactive period, the subcellular distribution of a number of nuclear proteins shifts from the cytoplasm to the nucleus of 1-cell embryos, and this nuclear translocation is correlated closely with the onset of embryonic transcription. Nuclear accumulation of general transcription factors, Sp-1 and the TATA box binding protein (TBP), the high-mobility group I non-histone chromosomal proteins (HMGI), and the largest subunit of RNA polymerase II (RPB1) occurs during the first cell cycle of 1-cell embryos [8][9][10]. We found recently that nuclear factor kappa B (NF-kB), a transcription factor, is transiently localized in the pronucleus of the mouse embryo at the early 1-cell stage and is exported to the cytoplasm as the 1-cell stage progresses [11].…”
mentioning
confidence: 99%
“…Cultured confluent ES cells were fixed with formalin for 15 min before ALP staining as described with 100 mM Tris-Hcl (pH 9.5) plus NBT (Sigma No.N-5514) and BCIP (Sigma No.B-0274) [24,25]. Immunostaining was performed with the following monoclonal antibodies: SSEA-1 (Chemicon, No.…”
Section: Identification Of Embryonic Stem Cellsmentioning
confidence: 99%